(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
In this article, the staging of the street show “Of the tasty adventures of Dom Quixote de La Mancha and his squire Sancho Pança – a chapter that could have been” (2006) (Das saborosas aventuras de Dom Quixote de La Mancha e seu escudeiro Sancho Pança – um capítulo que poderia ter sido) was discoursed, a free adaptation of the classic Dom Quixote de la Mancha (1605), by Miguel de Cervantes, directed by André Carreira. The objective is to understand the occupation of urban space as a scenic space, investigating the street as a dramaturgical possibility. For the analysis, the concept of Invasion Theater, proposed by André Carreira, was listed and the category of ‘organiCity’ was inaugurated. Therefore, semi-structured interviews were carried out with the director of the show and the members of the Teatro que Roda group, which were able to elucidate the process of creating the collective and the scenic composition proposed for the montage. It is understood that the occupation of this social space produces multiple layers of meaning of, for, with and through the street and demands expanding the notion of spatiality in the field of Performing Arts.